Подолання наслідків аварії Чорнобильської АЕС – головна проблема економіки природокористування Житомирської області - Матвійчук, В. В. (My University, 2013)
В статті розглядається екологічна ситуація регіону України, яка з року в рік погіршується, вагомим фактором чого є наслідки аварії на Чорнобильській АЕС, від якої постраждала саме Житомирщина. Understanding of the peculiarities of the Zhytomyr Region’s environmental status is very important for the study of the present-day economy of environmental management of the Region. A significant part of the Region’s lands has a high level of radioactive pollution as a result of the Chernobyl Nuclear Power station accident. Mining of mineral resources is another very important factor o f high radioactivity level. Most o f the deposits are situated on the Ukrainian Shield, which has natural high radioactivity level. All of this has led to the safety restrictions in economic activities on territories polluted by radio nuclides. Having analyzed the distribution of the enterprises-pollutants of the environment according to the type o f economic activity, one should state that, in spite of the decrease of the volume of production and depopulation, economic activity is the main factor of the Region’s ecological problems. At the same time, according to the data o f the State Board of Environmental Protection in the Zhytomyr Region, only four enterprises on its territory are engaged in utilizing and processing the ecologically harmful substances and materials, and this does not correspond to the needs of the Region.
Keywords: ecological situation; radioactive pollution; the environment; the chernobyl nuclear power plant; радіоактивне забруднення; навколишнє природне середовище; Чорнобільська АЕС; екологічна ситуація